Bone mineral density and fragility fractures in stroke patients - Povorozniuk, V. V.; Bystrytska, M. A.; Hryhorieva, N. V (Zaporozhye Medical Journal, 2019)
The aim was to study the parameters of bone mineral density (BMD) and frequency of fragility fractures in males and females with ischemic stroke depending on a side of brain injury and duration of post-stroke period. Materials and methods. We examined 140 patients aged 50–80 years old, divided into 2 groups: I – subjects without any diseases influencing the bone state and II – patients after ischemic stroke. BMD indexes (BMDs) were measured using dual-energy X-ray absorbtiometry method. Results. The males with stroke had significantly lower parameters of total body, upper extremity and trunk BMDs compared to indexes of the control group without any differences in lower extremities BMDs in contrast to women with stroke who had lower BMDs of total body, trunk and upper/lower extremities compared to parameters of the control group. Almost all measured BMDs were significantly lower on a paretic side compared to BMDs on a non-paretic side, except distal radius and total lower extremities BMDs in men with stroke in contrast to women who demonstrated significantly lower femoral neck and total femur BMDs compared to the control group. Most BMDs were decreased in females with post-stroke period duration of more than 1 year in contrast to data in men who did not show any BMD differences, except significantly decreased BMD of upper extremities compared to the control group. Fragility fractures were revealed in 21.4 % of patients after stroke (31.8 % in women and 10.0 % in men, P < 0.05), their frequency was higher only in women compared to the control group patients. Conclusions. BMDs in stroke patients are lower and frequency of osteoporosis is higher with some sex differences that should be taken into account in their assessment and development of rehabilitation programs for older age subjects.